The Application Effect of Endoscopic Thyroidectomy via the Gasless Unilateral Axillary Approach in Thyroid Cancer and Its Impact on Postoperative Stress Response - Jinliang Jia; Jihua Han; Rui Pang; Wen Bi; Bo Liu; Ruinan Sheng; Lingyu Kong (Current Oncology)
Objective: This study aims to evaluate the application effect of endoscopic thyroidectomy via the gasless unilateral axillary (GUA) approach in thyroid cancer and its impact on the postoperative stress response. Methods: Ninety-four thyroid cancer patients were enrolleod and assigned into the open group (underwent conventional-open-anterior-cervical-approach thyroidectomy) and the endoscopic group (underwent GUA endoscopic thyroidectomy) (n = 47). Perioperative indicators between the two groups were compared. Thyroid function parameters [total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3), free thyroxine (FT4), and thyroid-stimulating hormone (TSH)] were measured preoperatively and on postoperative day 2. Inflammatory markers [interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α)] and stress-related hormones [norepinephrine (NE) and cortisol (Cor)] were evaluated preoperatively and on postoperative day 1. The aesthetic appearance of the incision was evaluated at 1 and 3 months postoperatively using the Vancouver Scar Scale (VSS). Postoperative complications were also compared between the two groups. Results: The endoscopic group exhibited less intraoperative blood loss, reduced postoperative drainage, a lower pain degree on 1 day postoperatively, a shorter hospitalization time, and a longer surgical time versus the open group (p < 0.05). The serum levels of TT3, TT4, FT3, and FT4 were lower, while the TSH levels were higher in both groups on postoperative day 2 compared to preoperative values. Additionally, the serum levels of IL-6, TNF-α, NE, and Cor increased on day 1 postoperatively, with the endoscopic group showing lower levels of these markers compared to the open group (p < 0.05). The VSS scores at 1 and 3 months after surgery were lower in the endoscopic group compared to the open group, indicating better cosmetic outcomes (p < 0.05). The incidence of postoperative complications was comparable between the endoscopic and open groups (p > 0.05). Conclusions: Endoscopic thyroidectomy by a GUA offers notable advantages over the conventional-open-anterior-cervical-approach thyroidectomy, including reduced intraoperative blood loss, less postoperative drainage, and a lower postoperative stress response. This approach also results in improved cosmetic outcomes, making it a promising alternative for thyroid cancer surgery.